Platinum desensitization therapy and its impact on the prognosis of ovary high-grade serous adenocarcinoma: a real world-data - Li, Kemin; Yin, Rutie (Frontiers in Immunology, 2024)
Background: To examine the value of five-step platinum desensitization therapy in epithelial ovarian cancer Methods: A retrospective study was conducted on the high-grade serous adenocarcinoma of the ovary (HGSAO) patients who developed a platinum allergy during treatment and received desensitization therapy between January 2016 and December 2020. The logistic-regression was adopted to analyze the relationship between platinum desensitization therapy and prognosis in HGSAO patients. Results: 92 HGSAO patients were included in the study. Among these, 35 patients (38.0%) experienced mild allergic reactions, 51 (55.4%) experienced moderate allergic reactions, and 6 (6.5%) experienced severe allergic reactions. The desensitization therapy was successful in 86 patients (93.5%). Six patients had desensitization failure, of which five experienced severe allergic reactions during desensitization. The logistic-regression analysis revealed no significant correlation between platinum desensitization therapy and progression-free survival (PFS) or overall survival (OS) of patients (P < 0.05). However, the subgroup analysis demonstrated that the success or failure of platinum desensitization therapy significantly impacted the OS of patients who were platinum-sensitive recurrence. The patients who had successful desensitization therapy had a superior OS. Conclusion: Five-step platinum desensitization therapy has potential application value in patients who were platinum-sensitive recurrence after first-line treatment but may bear the risk of severe allergic reactions.